Tectonic Boundaries and Depth Estimate of Some Gravity Sources in Diyala Area, East Central Iraq - AL-Banna, Ahmed S.; Daham, Alaa N. (Iraqi Journal of Science, 2019)
The Bouguer gravity and magnetic RTP anomalies data were used to detect the main tectonic boundaries of middle and south of Diyala Province, east Iraq. Window method was used to separate the residual anomalies using different space windows for the Bouguer and Magnetic RTP maps. The residual anomaly processed in order to reduce noise and give a more comprehensive vision about subsurface lineaments structures. Results for descriptive interpretation presented as contour maps in order to locate directions and extensions of lineaments feature which may interpret as faults. The gradient technique is used for depth estimation of some gravity source which shows that the sources depth range between (13.65 - 5.36) km. Some gravity sources confirms the depth of basement rocks, while other shallow sources related to sedimentary cover, on an assumption of body source approximated to a horizontal cylindrical. The Total Horizontal Derivative (THD) technique is used to identify the faults trends in the sedimentary cover and basement rocks depending upon gravity and magnetic data. The identified faults in the study area show (NW-SE),(NE-SW) and(N-S)trends. Most faults extending from the basement to the upper most layer of the sedimentary cover rocks. Depending on the detected faults, the main tectonic boundaries of the region were obtained.